Mak Yong’s Performing Art: A Collection Analysis of Malaysia Institutional Memory - Mazlina Pati Khan; Andika Aziz Hussin; Khairul Azhar Mat Daud; Nordiana Mohd Nordin (Record and Library Journal, 2022)
Background of the study: Documentation is an imperative initiative in safeguarding Intangible Cultural Heritage (ICH) to consolidate and nurture appreciation that is intact to culture and heritage within a society. However, many countries in the world still give less attention to documenting heritage systematically. Purpose: This study aims to achieve a greater exposure of Institutional Memory’s in Malaysia play a role in preserving and conserving heritage information on Intangible Cultural Heritage (ICH) through the documentation strategy of Mak Yong’s performing art collection. Method: This study adopted a case study approach by pertaining qualitative research method. Qualitative data were gathered through content analyses towards 521 of Mak Yong’s performing art collection were carried out in three (3) Malaysia Institutional Memory. Findings: The study found that the lack of Mak Yong’s collection in institutional memories is contributed to some elements that require detailed documentation such as characters, spectacle, diction, and sound. Conclusion: safeguarding of ICH through preservation and conservation of Mak Yong’s information collection that still needs to be improved by considering the consolidation of integrated institutional memory’s roles and ongoing implementation of documentation strategy program of heritage information.